Necrolytic migratory erythema associated with hyperglucagonemia and neuroendocrine hepatic tumors - Marko, Pij B. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
We present a 61-year-old man with a 2-year history of persistent disseminated, psoriasiform annular pruritic lesions, acrodermatitis, weight loss, anemia and diabetes. Histopathology of the affected skin showed nonspecific subacute psoriasiform dermatitis. The computed tomographic scan of the abdomen revealed multiple hepatic tumors. Histopathological examination of ultrasound-guided needle biopsy from a hepatic lesion demonstrated a neuroendocrine tumor. Somatostatin-receptor scintigraphy with radio-labelled octreotide confirmed the likelihood of the neuroendocrine nature of the hepatic tumors and excluded the presence of other such lesions throughout the rest of the body, including the pancreas. The serum glucagon level was markedly increased. The diagnosis of necrolytic migratory erythema associated with hyperglucagonemia and neuroendocrine hepatic tumors was made and therapy with the long-acting somatostatin analogue octreotide was started. The skin changes resolved after the initiation of therapy, but no improvement of other symptoms was observed. Having reached the final stage of the disease, which was further complicated by congestive heart failure, the patient died one year later. As no autopsy was performed, we were unable to establish whether the hepatic tumors represented a metastatic process of previously undetected pancreatic glucagonoma or if they were extra-pancreatic glucagon-secreting tumors. The correct diagnosis of necrolytic migratory erythema is important, since it might be the clue for early detection of glucagonoma or of extra-pancreatic glucagon-secreting tumors.
Keywords: dermatologija; Diabetes mellitus; Eritem; Erythema; Glucagon; Glukagon; Jetra; kožne spremembe; Liver; Neuroendocrine tumors; Nevroendokrini tumorji; Octreotide; Oktreotid; Sladkorna bolezen; tumorji